2012
DOI: 10.1007/s12272-012-0812-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of sargachromanol G isolated from Sargassum siliquastrum in RAW 264.7 cells

Abstract: A study on the anti-inflammatory activity of brown alga Sargassum siliquastrum led to the isolation of sargachromanol G (SG). In this study, the anti-inflammatory effect and the action mechanism of SG have been investigated in murine macrophage cell line RAW 264.7. SG dosedependently inhibited the production of inflammatory markers [nitric oxide (NO), inducible nitric oxide synthase (iNOS), prostaglandin E(2) (PGE(2)), and cyclooxygenase-2 (COX-2)] and pro-inflammatory cytokines [tumor necrosis factor-α (TNF-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
0
46
0
1
Order By: Relevance
“…The MAPK pathways, containing three parallel kinase modules p38, JNK and ERK1/2, play a principal role in the regulation of iNOS and inflammatory cytokine production in RAW 264.7 cells exposed to LPS [35,36]. In general, the activation of p38 is required for the expression of a large number of inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathways, containing three parallel kinase modules p38, JNK and ERK1/2, play a principal role in the regulation of iNOS and inflammatory cytokine production in RAW 264.7 cells exposed to LPS [35,36]. In general, the activation of p38 is required for the expression of a large number of inflammatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that paeonol, M3, and M11 suppressed the high expression of iNOS protein in a dose-dependent manner, which strongly suggested that the decrease in NO production was due to the suppression of iNOS expression. Previous studies have shown that MAPK signaling pathway plays an important role in the regulation of iNOS and COX-2 expression, and in pro-inflammatory cytokine production in LPSactivated macrophages [23][24][25]. Our results indicated that paeonol, M3, and M11 strongly blocked the phosphorylation of MAPK/ERK and MAPK/p38 proteins but showed no obvious inhibition on the phosphorylation of MAPK/JNK protein, which suggested that the suppression on MAPK/ERK/p38 signal pathway may contribute to the anti-inflammatory effect of paeonol and its metabolites such as M3 or M11.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory activity has been reported for a range of other algal metabolites isolated from non-polar and DCM extracts including the chromene sargachromanol G from the Korean brown alga Sargassum siliquastrum (order Fucales) (Yoon et al 2012); halogenated compounds from the Malaysian red alga Laurencia snackeyi (Vairappan et al 2013) and the porphyrin derivatives, pheophorbide a and pheophytin a, along with the xanthophyll fucoxanthin, from the edible brown alga Saccharina japonica (order Laminariales) (Islam et al 2013). Other bioactive algal metabolites isolated from non-polar extracts include cytotoxic, antibacterial linear sesquiterpenoids from the green alga Penicillus capitatus (class Ulvophyceae, order Bryopsidales) (Paul and Fenical 1984); antibacterial labdane diterpenoids from Ulva fasciata (Chakraborty et al 2010); and antiatherosclerotic phytosterols from the brown alga Sargassum fusiforme (order Fucules) (Chen et al 2014).…”
Section: Discussionmentioning
confidence: 99%